Earnings quality and equity returns : evidence of the accrual anomaly from the South African equity market - Lutchmun, Thashveen (Rhodes University, Faculty of Commerce, Department of Accounting, 2015)
A key incentive for accounting research is to provide evidence on the usefulness of earnings in making economic decisions. Of particular interest over the last two decades is the issue of the quality of financial reporting, specifically the quality of earnings, given the number of global financial scandals reported during that period. The quality of earnings is driven by the choices, estimates and judgments that the accounting standards make available to managers in order to portray the firm's economic position and performance in a timely and credible manner. However, this leeway in financial reporting also creates opportunities for earnings management. The objective of this thesis is firstly to establish whether earnings manipulation has had the ability to predict cross-sectional returns in South Africa during the 2007-2014 period. In other words, the purpose of this thesis is to find evidence whether the market reacts to earnings management practices, as measured by accruals, and rewards high earnings quality companies with higher equity returns (a process known as the accrual anomaly). The timeframe selected for the research encompasses the global financial crisis, a period in which accounting manipulation incentives are likely to be strong. Secondly, this study attempts to establish the presence of the accrual anomaly amongst growth and value firms. The motivations for earnings management of the former are expected to be strong. Securities are allocated to portfolios according to accruals and the subsequent equity returns are analysed cross-sectionally to establish the existence of the accrual anomaly and hence assessing the usefulness of earnings manipulation in predicting equity returns. To provide evidence for the presence of the accrual anomaly amongst growth and value shares, securities are independently allocated to portfolios according to their book-to-market ratio and accruals and a cross-sectional analysis is performed on their subsequent equity returns. In order to increase the robustness of the tests, two measures of accruals are used: a balance sheet approach and a cash flow measure. Evidence is provided for the presence of the accrual anomaly among South African listed companies for the balance sheet measure of accruals but not the cash flow approach. Whilst the accrual anomaly is significantly present in a growth-neutral-value construct, statistical significance is not established when growth and value shares are considered individually.
Keywords: Earnings management -- South Africa; Accounting -- Standards